Effect of Titanium Dioxide Nanoparticle on Properties of Nanocomposite Membrane Made of Bacterial Cellulose - Uun Yanuhar; Heru Suryanto; Susanto Arif Sardjono; Irma K. Ningrum; Aminnudin Aminnudin; J S Binoj (Journal of Natural Fibers, 2022)
The purpose of this study was to see the effect of adding TiO2 nanoparticles had on the characteristics of bacterial nanocellulose (BNC)-based membranes. Pellicles were created from the pineapple peel waste extract, and to obtain BNC, pellicle was disintegrated in six cycles using high-pressure homogenizer at 150 bar. The concentrations of TiO2 nanoparticles in the membrane reinforcement solution were 0.5, 1.0, 1.5, 2.0, and 2.5 wt.%. They were sonicated and dried in an oven at 60°C for 8 h. X-ray diffraction, Fourier transform infrared spectroscopy, roughness test, mechanical properties, and scanning electron microscopy were investigated to explore its claims. The results revealed that diffraction pattern of BNC/TiO2 membrane has a new peak at 25.05° that ensures the presence of TiO2 nanoparticles as well as diffraction peak occurred at 22.49°, which indicates the presence of cellulose Iβ. Moreover, the addition of TiO2 nanoparticles until 1.5 wt.%, the crystallinity index is relatively same and the optimum strength of 99.5 MPa was attained. Further, improvement in addition of TiO2 nanoparticle at 2 wt.% showed a decline in crystallinity index as 80.16% to 74.72% at 2.5 wt.%. The morphology of the membrane surface revealed that TiO2 nanoparticles were still agglomerated and not equally distributed across the BNC membrane, leading to increase in surface roughness.